PERILAKU TRENGGILING (Manis javanica, Desmarest, 1822) DAN KEMUNGKINAN PENANGKARANNYA - Burhanuddin Masy'ud; Novriyanti .; M. Bismark (Department of Forest Resources Conservation and Ecotourism - IPB University, 2011)
Pangolin (Manis javanica, Desmarest 1822) has believed by many peoples as food and medicine who have a high economic value, so demand of pangolin tend increase. Wild harvesting from natural habitat are the way always used to supply of demand, and this was affecting to wild population has been decrease significantly. Captive breeding programs in the ex situ area is the best alternative solution to support the demand sustainability and its conservastion in natural habitat. The question is, “ did success possibilities to captive breeding? Based on the study have been done about animal behaviour and implementation of some technical of captive breeding program,we would like to say that the captive breeing program of pangolin could be success. Key words: pangolin, behaviour, daily activities, captive breeding